Asian Ethnicity and Femoral Geometry in Atypical Femur Fractures: Independent or Interdependent Risk Factors?. (17th February 2022) - Dhanekula, Nitesh D; Crouch, Gareth; Byth, Karen; Lau, Sue Lynn; Kim, Albert; Graham, Edward; Ellis, Andrew; Clifton‐Bligh, Roderick J; Girgis, Christian M
ABSTRACT: The earliest reports of atypical femur fractures (AFF) emerged from Asia. In the West, epidemiologic studies report a greater incidence of AFFs among subjects of Asian background. Asian ethnicity is an established risk factor for AFF, but clear mechanisms to explain this risk and implications for the general development of AFF are open questions. Ethno‐specific differences in bisphosphonate action and femoral geometry have been proposed as hypotheses. In a retrospective cohort of 163 female patients presenting with AFFs or typical femur fractures (TFF), relative contributions of Asian ethnicity, proximal femoral geometry, and bisphosphonate use in AFF status were examined. There was a fourfold higher proportion of Asian subjects in the AFF compared with TFF groups (31.6%, 30/95 versus 7.4%, 5/68). Asian subjects had smaller femurs in femoral head, neck, and axial dimensions. A multiple logistic regression model for AFF status was fitted adding Asian ethnicity to three previously reported independent predictors of AFF including femoral geometry, which together comprise the Sydney AFF Score (age ≤80 years, femoral neck width <37 mm than non‐Asian, lateral cortical width at lesser trochanter ≥5 mm). Asian ethnicity was a robust independent predictor of AFF, imparting sevenfold increase in the odds of AFF after adjusting for all three variables (95% confidence interval [CI] 2.2–23.2, p = 0.001) or for overall AFF score (95% CI 2.2–22.3 p = 0.001). Overall Asian subjects had higher rates of bisphosphonate use than non‐Asian subjects (67.6% versus 47.2%, p = 0.034). Among AFF bisphosphonate users, Asian subjects had lower AFF scores than non‐Asians (Sydney AFF Score ≤1, 45.5% Asian subjects versus 22.2% non‐Asian subjects, p = 0.05). Asian ethnicity is a strong independent risk factor for AFF, unaccounted for by ethno‐specific differences in proximal femoral geometry. Bisphosphonate use may be associated with a greater predisposition for AFF in Asian subjects compared with non‐Asian subjects. © 2022 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.